2016
DOI: 10.1371/journal.pone.0155495
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell Free DNA as the Diagnostic Marker for Ovarian Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundQuantitative analyses of circulating cell-free DNA (cfDNA) are potential methods for the detection of ovarian cancer. Many studies have evaluated these approaches, but the results were too inconsistent to be conclusive. This study is the first to systematically evaluate the accuracy of circulating cfDNA for the diagnosis of ovarian cancer by conducting meta-analysis.MethodsWe searched PubMed, Embase, Cochrane Library and the Chinese National Knowledge Infrastructure (CNKI) databases systematically fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 42 publications
1
58
0
1
Order By: Relevance
“…Regarding temporal heterogeneity, some studies of high-grade ovarian serous cancer show that most clonal characteristics evident in recurrent or metastatic disease are present as subclonal populations within the primary tumor [40,49,52], although one study showed evidence of ongoing tumor evolution [51]. In this context, it is worth noting that assays for sequencing tumor cell-free circulating DNA from the bloodstream, while still evolving, have the potential to detect ovarian cancer at an early stage, to provide simultaneous genomic information on multiple tumor foci and to reveal ongoing changes in tumor genomic characteristics that occur following surgery and subsequent therapy, thereby circumventing many of the limitations imposed by direct sampling of heterogeneous tumors [54]. In addition, next-generation/high throughput sequencing studies of STIC specimens may provide an opportunity to uncover molecular processes involved in tumorigenesis and the development of tumor heterogeneity in the setting of high-grade serous ovarian cancer [7].…”
Section: Ovarian Cancer As a Heterogeneous Diseasementioning
confidence: 99%
“…Regarding temporal heterogeneity, some studies of high-grade ovarian serous cancer show that most clonal characteristics evident in recurrent or metastatic disease are present as subclonal populations within the primary tumor [40,49,52], although one study showed evidence of ongoing tumor evolution [51]. In this context, it is worth noting that assays for sequencing tumor cell-free circulating DNA from the bloodstream, while still evolving, have the potential to detect ovarian cancer at an early stage, to provide simultaneous genomic information on multiple tumor foci and to reveal ongoing changes in tumor genomic characteristics that occur following surgery and subsequent therapy, thereby circumventing many of the limitations imposed by direct sampling of heterogeneous tumors [54]. In addition, next-generation/high throughput sequencing studies of STIC specimens may provide an opportunity to uncover molecular processes involved in tumorigenesis and the development of tumor heterogeneity in the setting of high-grade serous ovarian cancer [7].…”
Section: Ovarian Cancer As a Heterogeneous Diseasementioning
confidence: 99%
“…The discrepancies probably occur due to the different methods and pre-analytical conditions, the use of serum instead of plasma by some researchers and the different volumes of plasma/serum for cfDNA extraction. Many studies focused on the potential use of cfDNA as a diagnostic, prognostic and predictive biomarker in ovarian cancer and a recent meta-analysis by Zhou et al attempted to evaluate the role of cfDNA in ovarian cancer diagnosis [41]. An overview of the research studies on cfDNA in ovarian cancer is summarized in Table 2.…”
Section: Cell-free Dna (Cfdna)mentioning
confidence: 99%
“…Currently, the assessment of cell‐free nDNA or mtDNA in different body fluids has gained attention in many areas of medicine . For example, in obstetrics, maternal blood cell‐free nDNA of fetal origin has been mainly used for noninvasive prenatal diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Currently, the assessment of cell-free nDNA or mtDNA in different body fluids has gained attention in many areas of medicine. [19][20][21][22][23] For example, in obstetrics, maternal blood cell-free nDNA of fetal origin has been mainly used for noninvasive prenatal diagnosis. 20 Additionally, its levels have been shown to be increased in various pregnancy complications such as miscarriage, preeclampsia, fetal growth restriction, and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation